Acceptance and psychological change at the higher levels of care: A naturalistic outcome study. Issue 4 (4th July 2018) - Walden, Keegan; Manwaring, Jamie; Blalock, Dan V; Bishop, Emmett; Duffy, Alan; Johnson, Craig
ABSTRACT: This naturalistic outcome study reports on psychological change among a large ( N = 617), transdiagnostic sample of eating disordered adults treated at higher levels of care at a private facility. Patients were assessed at admission and discharge for eating disorder psychopathology, depression, personality, and acceptance. Effect sizes ranged from d = .29 to d = 1.29, and the majority of participants (58.2%) were treatment responders, with BN patients showing a higher response rate than AN-R patients. Increased acceptance over the course of treatment was strongly associated with decreased eating disorder risk and may be an important factor in recovery.